3x+6
3x - 6 = -3x + 36Add 3x to each side:6x - 6 = 36Add 6 to each side:6x = 42Divide each side by 6:x = 7
3x = 18divide both sides by 3x = 6
y = -1x/2 3x + 6y = 0 -3x -3x __________ 6y = 0 - 3x --- -------- 6 6 y= -3x/6 y= -1x/2
5x-2 = 3x-6 5x = 3x - 6 +2 5x = 3x - 4 5x - 3x = -4 2x = -4 x = -2
If you mean -2y = 6x-6 then it is a straight line equation that can be simplified to y = -3x+3
Neither y3x-3 nor 3x-y3 are equations, and so neither of them can have a solution. Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. And using ^ to indicate powers (eg x-squared = x^2).
3x+6
If you mean: 3x-(2x+4x-6) then 3x-2x-4x+6 simplifies to 6-3x
6-3x+12=0 6+12-3x=0 18-3x=0 18=3x x=6
3x-6y=9 -3x -3x -6y=9-3x __ ____ -6 -6 y=9-3x ____ -6
3x + 2 = 3x + 6 This is not possible.
There is no property that justifies it. The equation is true for some values of x, not for others.
3x-3 = 6 3x = 6+3 3x = 9 x = 3
3x - 6 = -3x + 36Add 3x to each side:6x - 6 = 36Add 6 to each side:6x = 42Divide each side by 6:x = 7
(y - 6)(y2 + 6y + 36)
3x = 18divide both sides by 3x = 6